'Cashing In' on curiosity and spectacle: the forensic patient and news media. Issue 5 (2nd September 2016) - Morley, Sharon; Taylor, Paul
Abstract: Health and social care professionals are gatekeepers to, and custodians of, confidential service user information. In the United Kingdom (UK), police investigations have unveiled cases of payments being made to public service officials by journalists in return for service user information. The purpose of this discussion is to investigate such cases in the context of high-security forensic care. This paper provides a discussion drawing upon two UK-based case studies of prosecutions of public service workers relating to the sale of confidential information. The analysis presented here illuminates upon the salient and connected issues at work that have led to the transgression of legal obligations and professional responsibilities/principles of confidentiality. A fuller reading of the context in which these transgressions occur, and motivations that exist, may well serve to inform policy, training, guidance or vigilance in relation to the preserving of service user information in the future.